Impact analysis of constructed wetland for wastewater management in Rwanda - Nsanzabaganwa, Justin; Chen, Xi; Liu, Tie; Mupenzi, Christophe; Hakorimana, Egide; Mind'je, Richard; Mujawayezu, Marie Louise; Gasirabo, Aboubakar; Umugwaneza, Adeline; Malayika, Flora; Niyonsenga, Schadrack (Frontiers in Environmental Science, 2025)
Constructed wetland (CW) is cost-effective, easy to operate, maintain, and offer significant natural potential for application in urban areas compared to conventional treatment systems. Despite their effectiveness in wastewater management, CWs have yet to see widespread adoption in Rwanda. This study aimed to analyze the impact of constructed wetland for wastewater treatment located in Gasabo district, Kigali City of Rwanda for water pollution dipping by testing eight physico-chemical parameters such as: pH, TN, TP, TSS, TDS, COD, BOD, and DO in the samples collected at the influents and effluents of the CW during rainy and dry seasons in twelve months of year 2023, relating their concentrations with standards of the World Health Organization (WHO), determining the CW removal efficiency and finally, to provide summary of measurement by the CCME-WQI. The results revealed that, the most parameters have been exceeding the standards before being treated, then after all effluents responded to standard conditions. The removal efficiencies in both seasons valued between 16-80% which presented a good concert in treatment. Furthermore, the index showed a high pollution on influent which was counted 42.1 and 46.4 in both dry and rain seasons respectively as poor and marginal quality, on the other side of effluent the results indicated 87.7and 89.1 ranked as good quality. These above values demonstrated the effective performance of constructed wetland regarding the production of the effluent that met the specified water quality standard despite elevated influent concentrations in terms of pollutants. Further application of CW in other organizations/institutions (public and private) is greatly suggested to treat their wastewater before reaching water flows in the environment.